Project based learning of embedded systems - Davchev, Dancho; Risteska Stojkoska, Biljana; Kalajdziski, Slobodan; Trivodaliev, Kire (My University, 2016)
Traditional teaching, usually based on lectures and tutorials fosters the idea of instruction-driven learning model where students are passive listeners. Besides this approach, Project Based Learning (PBL) as a different learning paradigm is standing behind constructivism learning theory, where learning from real-world situations is put on the first place. The purpose of this paper is to present our approach in learning embedded systems at our University. It is based on combination of traditional (face-to-face) learning and PBL. Our PBL represents an interdisciplinary project based on wireless sensor monitoring of real-world environment (greenhouse). The students use UML that was shown as an excellent tool for developing such a projects. From the student perspective, we found that this high level of interdisciplinary is very valuable from the point of view of facing the students with reallife problems.
Keywords: Wireless Sensor Networks, Project Based Learning, Embedded Systems